Advances in bionanomaterials : selected papers from the 2nd Workshop in Bionanomaterials, BIONAM 2016, October 4-7, 2016, Salerno, Italy /: selected papers from the 2nd Workshop in Bionanomaterials, BIONAM 2016, October 4-7, 2016, Salerno, Italy. ([2018]) - Unknown
No abstract available